Awareness, Attitudes, and Practices of High School Students Toward Eco-Friendly Products - Jovia , Ma. Lynneth Ann; Pagulayan , Aliah Nicole; Han , Zhi Cheng; Royo , Aftiel; Vino , Angelika Ann; Ramos, Rowena Imelda; Ibañez, Mercedez; Carolino , April; Laguador , Perfecta; Asi, Gerardo (12th International Scholars Conference 2025, 2026)
- This study examined the awareness, attitudes, and practices of high school students toward eco-friendly products. With the escalating environmental challenges, understanding the younger generation’s behaviors is essential for promoting sustainability. Using a descriptive-correlational research design, data were collected from 250 students selected through cluster sampling. Findings reveal that students have demonstrated a high level of awareness of eco-friendly products, particularly their environmental benefits. However, knowing the relatively high cost of these products limits them. Students exhibit a generally positive attitude toward eco-friendly products, showing appreciation for their benefits, although their willingness to pay a higher price is lower. In terms of practices, students demonstrate good sustainable behaviors, often opting for durable products, though they are less likely to check for eco-friendly certifications. Correlation analysis shows that awareness and attitude are positively correlated to practices. Additionally, attitudes emerge significantly as a predictor of eco-friendly practices. The findings highlight the need to foster positive attitudes and address barriers such as the affordability of eco-friendly products. These results encourage efforts to cultivate environmentally responsible behaviors in the younger generation by enhancing positive attitudes toward eco-friendly products. Future research should investigate additional factors, such as socio- economic status and parental influence, to provide a more comprehensive understanding of sustainable consumption among students.